Discordance between serum anti-Müllerian hormone concentrations and antral follicle counts: not only technical issues. Issue 6 (24th April 2018) - Alebić, M Š; Stojanović, N; Dewailly, D
Abstract: STUDY QUESTION: Do patient-specific features contribute to the differences between measured serum anti-Müllerian hormone (AMH) concentrations and AMH values expected from the corresponding antral follicle count (AFC)? SUMMARY ANSWER: Patient-specific features contribute to the differences between measured AMH values and AMH values expected from the corresponding AFC (AMHp), potentially through their effect on follicular AMH production. WHAT IS KNOWN ALREADY: Both patient counselling and patient management could be hampered by finding of disagreement between AFC and AMH if both are used for the prediction of ovarian response. The difference between measured AMH concentrations and AMH values expected according to the corresponding AFC cannot be entirely explained by the technical limitations of counting of antral follicles and analytical variability of the AMH assay used. STUDY DESIGN, SIZE, DURATION: This retrospective study analysed medical records of 1097 IVF patients collected between March 2011 and July 2013. PARTICIPANT/MATERIALS, SETTING, METHODS: The study population ( N = 1097) included 705 (64.3%) women with normal ovarian morphology and 392 (35.7%) women with polycystic ovarian morphology, aged 20–44 years, who underwent their first IVF cycle in a single clinical centre. AMH was measured by a routine laboratory method and predicted AMH (AMHp) values were calculated using the linear regression equation (AMHp = −4.4 + 1.5 × AFC). The absolute value of the difference between AMH and AMHp was considered to be the measure of the degree of AMH–AFC agreement. The association of the difference between AMH and AMHp with clinical and biochemical parameters was investigated in both the higher-than-predicted (HTP) group comprising patients with AMH higher than AMHp ( N = 466) and the lower-than-predicted (LTP) group comprising patients with AMH lower than AMHp ( N = 631). MAIN RESULTS AND THE ROLE OF CHANCE: Patients in the HTP group had significantly longer menstrual cycle length and higher AMH and LH concentrations but lower AFC and FSH concentration than their counterparts in the LTP group. There was a significant association of absolute value of the difference between AMH and AMHp with age, menstrual cycle length, AFC, FSH and testosterone in both groups ( P < 0.001). The difference between AMH and AMHp was exclusively correlated to LH in the HTP group ( r = 0.159, P < 0.001) and to BMI in the LTP group ( r = 0.231, P < 0.001), respectively. Multiple regression analysis revealed that only LH was significantly related to the difference between AMH and AMHp in the HTP group, independently from AFC. In the LTP group, BMI, menstrual cycle length, FSH and testosterone were found associated with the difference between AMH and AMHp, independently from AFC. LIMITATIONS, REASONS FOR CAUTION: The main limitation of the study is selection bias. Data analysed in this study were collected from medical records of patients undergoing IVF treatment in a single department of human reproduction which precludes generalization of the results to women of different geographic origin, ethnicity, race and reproductive status. WIDER IMPLICATION OF THE FINDINGS: AMH higher than expected for a given AFC could suggest up-regulated AMH secretion (a typical feature of polycystic ovary syndrome) while AMH lower than expected from the corresponding AFC suggest down-regulated AMH secretion that could be seen as an early symptom of diminished ovarian reserve and premature ovarian insufficiency. In other words, when challenged against AFC, the serum AMH level is not only a quantitative but also a qualitative follicle marker, in relation with clinical and endocrine parameters. STUDY FUNDING/COMPETING INTEREST(S): No study funding was obtained for this study. The authors have no conflict of interest(s) to declare. TRIAL REGISTRATION NUMBER: Non-applicable.